Assessment of Directional–Hemispherical Reflectance of Tablets with Cefuroxime during Storage under Elevated Temperature and Ultraviolet Radiation - Michał Meisner; Beata Sarecka-Hujar (Sensors, 2024)
Environmental conditions can lead to changes in the physical and chemical structures of drug products. In this study, the stability of cefuroxime tablets stored under adverse conditions was evaluated based on total directional–hemispherical reflectance (THR). The THR value was measured before and after the tablets’ exposure to stress factors (temperature of 45 °C and UV radiation). Each measurement was performed three times within seven spectral bands at the beginning of the experiment (day 0), and then on days 1, 2, 3, 5, and 7. In addition, hyperspectral profiles (400–1030 nm) were analyzed on days 0 and 7. A significant decrease in THR values in all wavelength ranges was observed when day 7 vs. day 0 were compared, especially for spectral bands of 335–380 nm and 1700–2500 nm (Δ = 0.220, p < 0.001 and Δ = 0.171, p < 0.001, respectively). The hyperspectral analysis confirmed a decrease in the reflectance after the end of stress conditions in the visible light range (400–700 nm) compared to tablets before the experiment. This may indicate that more radiation entered the tablets. In conclusion, the THR of cefuroxime tablets decreases during the exposure to heat and UV radiation, which may result from some physicochemical changes that have occurred during storage.